Predictors of work injuries: a quantitative exploration of level of English proficiency as a predictor of work injuries in the construction industry - McConnell, C. William, author; Gilley, Jerry, advisor; Gloeckner, Gene W., advisor; Schwebach, Robert, committee member; Gilley, Ann, committee member (Colorado State University. Libraries, 2004)
As evidenced by the literature review, there are both labor shortages and language barriers present in some areas of the construction industry. These issues translate into the higher than average accident and death rates seen among workers of Hispanic origin. Because of the increase in the Hispanic portion of the workforce, as indicated by reviewing census data, many Spanish-speaking individuals are taking jobs where they may not understand job hazards. In order to address these concerns, an instrument was developed to identify level of English proficiency. This was then linked to the injuries sustained on the job in the last 30 days as indicated by the body diagram. Participants were ranked on their level of English proficiency, and then divided into two groups. The middle group of predominately bilingual individuals was removed in order to maximize the differences between the two groups. There were a total of 191 participants in this study. The two groups were then compared based on the different independent variables identified in the research questions, as well as other possible relationships of interest as identified in the auxiliary findings section. The overall findings of this research indicate that there is not a significant difference in work injuries when based on level of English proficiency. In fact, in relation to this study, the more English proficient individuals were, the more likely they were to experience more injuries. This finding contradicts some areas in the literature that identify Spanish speaking individuals as having a higher accident rate than their more English speaking counterparts. Although no significant difference was identified between the two groups, based on level of English proficiency, there were many significant findings in both the primary research questions, as well as the auxiliary findings. Additionally, qualitative data obtained by the instrument provided insight into concerns that workers had relating to air quality that were not identified by looking just at the quantitative data. The body diagram also provided valuable information regarding frequency and location of injuries which will be beneficial in taking proactive actions toward reducing work injuries.
Keywords: vocational education